The politically incorrect guide to American history - Woods, Thomas E. (Washington, D.C. : Regnery Pub. ; Lanham, Md. : Distributed by National Book Network, 2004)
Looks at American history with an irreverant and hard-hitting look at the nation's important people and events, concluding that the American Revolution was fought by conservatives and the First Amendment accepted state-sponsored churches.
Includes bibliographical references and index.
Keywords: United States -- History -- Miscellanea; Political correctness -- United States